GAMBARAN PENGETAHUAN IBU HAMIL TENTANG KEKURANGAN ENERGI KRONIS (KEK) DI KLATEN - Isnani Nurhayati; Anas Rahmad Hidayat; Tri Hartati (JURNAL RISET GIZI, 2020)
Background : The need during pregnancy affects the nutritional status of pregnant women due to lack of intake in one of the substances will lead to the need for something impaired nutrients and the need for nutrients that are not constant during gestation. Unbalanced nutritional consumption in pregnant women will result in nutritional problems such as chronic energy deficiency (KEK) that will allow miscarriage, premature birth, BBLR and bleeding after childbirth.Objective : knowing the knowledge of pregnant mothers about chronic energy deficiency in Kebondalem Lor District Puskesmas Klaten Regency.Methods : This research is a descriptive analytic with a crosssectional approach. Population is all expectant mothers in Kebondalem Lor District Puskesmas in Klaten Regency as much as 167 people. Sampling with sample clusters obtained 42 respondents. Instruments using Quesioner contain knowledge of expectant mothers about chronic energy deficiency. Univariic data analysis is the frequency distribution of pregnant women knowledge about KEK, where the research results are conducted interpretation of the data of the question ite m by calculating the answer percentage.Result : From 42 expectant mothers of pregnant women knowledge about chronic energy deficiency are largely a good as much as 18 people (42.9%) and a small portion of respondents 9 people (21.4%) Less knowledgeable.Conclusion : The knowledge of pregnant women about chronic energy deficiency in the area of KebondalemLor District, Klaten Regency most are knowledgeable well.